The accumulation of active ingredients of Polygonatum cyrtonema Hua is associated with soil characteristics and bacterial community - Zhang, Qingyou; Cai, Yunzhang; Zhang, Luping; Lu, Mei; Yang, Luyun; Wang, Dekai; Jia, Qiaojun (Frontiers in Microbiology, 2024)
Introduction: With the increasing demand for health products derived from Polygonati rhizoma (PR), people begin to artificially plant Polygonatum cyrtonema Hua (P. cyrtonema) in the middle and lower reaches of the Yangtze River. To promote P. cyrtonema cultivation and increase farmers' income, efforts are needed to understand the ways to obtain high-quality PR under artificial cultivation conditions. Methods: Rhizomes of artificial planting P. cyrtonema and rhizosphere soils were collected across five regions in Zhejiang Province, China.Subsequently, the contents of the main active ingredients of P. cyrtonema and soil properties were analyzed, and both rhizosphere and endophytic bacteria of P. cyrtonema were detected by 16S rDNA sequencing.The relationship between the active ingredients and soil properties, and the dominant bacteria were investigated by correlation analysis.The content of active ingredients of P. cyrtonema from the five regions varied significantly, especially polysaccharides and saponins.High-throughput sequencing demonstrated that Proteobacteria was the dominant bacterial phylum in all samples, and Burkholderia-Caballeronia-Paraburkholderia was the main endophytic bacterial genus in rhizome. In addition, the bacterial diversity and richness of rhizosphere soil samples were higher than those of rhizome samples. Soil physicochemical properties and enzyme activities were significantly different across regions,leading to notable variations in the community structures of rhizosphere and endophytic bacteria.Redundancy analysis (RDA) displayed that pH and urease (UE) were the major factors altering shifting rhizosphere bacteria community structure.Moreover, the composition and diversity of rhizome endophytic bacteria were principally affected by both soil physicochemical properties and soil enzyme activities. Soil properties and bacteria from rhizosphere soil and rhizome had a considerable impact on certain active ingredients in P. cyrtonema under artificial cultivation conditions after pearson correlation analysis. Polysaccharides were significantly correlated with nutrient-rich soil and endophytic bacteria, such as Burkholderia-Caballeronia-Paraburkholderia, Pseudomonas, Ralstonia, and Bacillus.However, flavonoids were associated with nutrient-poor soil.Saponins were positively correlated with OM and available phosphorous (AP) and were significantly negatively affected by rhizosphere bacterial communities.The study demonstrated that bacterial microorganisms were involved in the accumulation of active ingredients of P. cyrtonema together with soil physicochemical properties and enzyme activities, which provided a theoretical basis for the scientific and effective artificial cultivation of high-quality P. cyrtonema.